PERMINTAAN DAN KEPUASAN KONSUMEN RUMAH TANGGA DALAM MENGONSUMSI KECAP DI BANDAR LAMPUNG - Ariesman, Ludi Satria; Prasmatiwi, Fembriarti Erry; Indriani, Yaktiworo (Lampung University, 2015)
The objectives of this research were: to assess the demand of soy sauce at the household level and its influencing demand factors, to analyze the degree of satisfaction and the factors that influence consumer’s satisfaction in consuming soy sauce in Bandar Lampung. The study was conducted by a survey method in Beringin Raya Village of Kemiling Sub District and Sawah Brebes Village of East Tanjung Karang Sub District, Bandar Lampung. The number of samples in this research was 76 people who were taken by Simple random sampling method. The data collection was conducted from April to June 2014. The factors that influenced consumer demand were analyzed by Cobb Douglas Analysis Function; the satisfaction of degree was analyzed by Customer Satisfaction Index (CSI), whereas the factors that influenced satisfaction of household consumers was analyzed by Logistic Regression Analysis. The result of this research showed that the demand of soy sauce of the household consumer was 501 ml/month. The factors that influenced the demand of soybean sauce were the price of soybean sauce, the price of sugar, income level, and number of family members. A total of 53 consumers were satisfied with the performance of soy sauce. Factors that influenced the level of customer satisfaction were age, duration of consumption, the price of soy sauce, and location of purchase. Key words: consuming, demand, satisfaction, soybean sauce